Makna Grebeg Pancasila Sebagai Upaya Pelestarian Nilai Pancasila di Kota Blitar - Sakhila Febrianti Rahayu (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
The city of Blitar is a small city dubbed as the city of Patriarchs which has a culture, namely Grebeg Pancasila, which aims to commemorate the birthday of Pancasila. This research uses descriptive qualitative research in the form of research with case study method. The instrument used in this study was the researcher himself, with data collection techniques in the form of direct observation. From the findings of the data, it was found that the Grebeg Pancasila celebration is a cultural ceremony held by the people of Blitar. This was born as a result of social protests from artists and community leaders of Blitar, for fear of historical corruption on June 1 as the birth of Pancasila which was abolished. Grebeg Pancasila was held into five processions, each of which had its own value. Grebeg Pancasila aims to preserve Javanese culture and commemorate the birthday of Pancasila. In addition, the celebration of Grebeg Pancasila has implicit values ​​in it, namely the value of togetherness in the Blitar community, mutual cooperation, living in harmony and peace with mutual respect for religious differences and each person's background.